OFR-8(3)-76 Analysis Of Men, Materials And Supplies Handling Systems In Underground Metal And Non-Metal Mines - Volume II - Appendices Associated With Phase I Report ? Glossary (The National Institute for Occupational Safety and Health (NIOSH), 1975)
? CAGER, CAGE RIDER, CAGE TENDER, SHAFT MEN All of the above job titles are variously associated with the handling of men and material at hoist stations. Generally, these classifications of personnel are involved with riding cages with personnel and in hoisting supplies into the mine. Job titles and activity description will be defined in the respective chapters. ? FLOW CHART SYMBOLS [Vertical Transportation Horizontal Transportation Storage Operation Delay ]